"FROM ASSESSMENT TO CHANGE: A STRATEGY FOR SYSTEMATIC REFORMS IN SCHOOLS IN UZBEKISTAN BASED ON THE PISA CONCEPT" (Universal International Scientific Journal, 2026)
This thesis is devoted to identifying ways and promising strategies for the effective use of the experience of the international PISA study in the education system of Uzbekistan. Based on the analysis of the PISA 2022 results, systemic problems were identified and six strategic directions were developed based on the conceptual approach “from assessment to change”. The thesis substantiates the ways to adapt the experience of Finland, Estonia and Singapore to the national-cultural context of Uzbekistan and enter the top 30 in the PISA ranking by 2030.
Keywords: PISA, functional literacy, competency-based approach, formative assessment, teacher training, equality in education, digital transformation, education policy, systemic reforms, education system of Uzbekistan